Of Markets and Marriages: A Multidisciplinary, Multi-book Review Essay of Recent Work on the Causes of US Poverty - Ananat, Elizabeth Oltmans (Journal of Economic Literature, 2025)
How is it that in perhaps the richest country in the history of the world such a large number of people struggle to acquire the basic necessities of life? Clearly, merely increasing the total quantity of goods and services produced in the market does not address this core problem. I review new work both inside and outside of economics that seeks to understand the persistence of poverty in the United States. With a particular focus on Desmond (2023) and Kearney (2023), I draw out the hypotheses in this work, suggest interesting avenues for future research, and discuss potential policy implications. ( JEL I26, I32, I38, J12, J13, J24)